Preliminary Validation of Japanese Version of the Parental Burnout Inventory and Its Relationship With Perfectionism - Kawamoto, Taishi; Furutani, Kaichiro; Alimardani, Maryam (Frontiers in Psychology, 2018)
Parenting is a precious experience and also a very hard task, which could result in parental burnout for some parents. The present study sought to validate a Japanese version of the Parental Burnout Inventory (PBI-J) by replicating and extending the pioneering work of Roskam et al. (2017). We conducted a web survey (N = 1200) to first validate the PBI-J and second to investigate the association between the PBI-J and perfectionism as a new interrelation. Similar to the prior study of Roskam et al. (2017), confirmatory factor analysis supported a model of three-factor structure of the PBI-J: emotional exhaustion, lack of personal accomplishment, and emotional distancing. In addition, we found low to moderate correlations of parental burnout with job burnout, parental stress, and depression. These findings provided initial evidence for validity of the PBI-J and suggested that parental burnout appeared to be different from job burnout. Our further evaluation of perfectionism confirmed such a difference between parental and job burnout by showing that parental perfectionism [i.e., combination of parental personal standards (PS) and parental concern over mistakes (CM)] has a unique contribution to parental burnout than does job perfectionism (i.e., combination of job PS and job CM). In addition, CM was positively correlated with burnout in both domains whereas the associations between PS and burnout were more complex. Finally, the proportion of parents experiencing burnout was estimated to lie somewhere between 4.2 and 17.3% in Japan. Overall, the present study confirmed preliminary validity of the PBI-J and found that parental perfectionism is one of the vulnerability factors in parental burnout.